The role of melatonin in the development of postmenopausal osteoporosis - Yang, Keda; Qiu, Xueshan; Cao, Lili; Qiu, Shui (Frontiers in Pharmacology, 2022)
Melatonin is an important endogenous hormone that modulates the homeostasis of microenvironment. Recent studies indicated serum melatonin level was closely associated with the occurrence and development of osteoporosis in postmenopausal women. Exogenous melatonin could also improve bone mass and increase skeletal strength. In order to determine the mechanism for the prevention and treatment of postmenopausal osteoporosis with melatonin, we made this review to analyze the role of melatonin in bone metabolism according to the physiology function of melatonin. Serum melatonin was related to the bone mass, the measurement of which was a potential method for the diagnosis of osteoporosis. And melatonin had a direct effect on bone remodeling for promoting osteogenesis and suppressing osteoclastogenesis. Melatonin also regulated the biological rhythm of bone tissue which was positive to its osteogenic effect. Additionally, melatonin participated in the modulation of bone microenvironment. Melatonin attenuated the damage of oxidative stress and inflammation on osteoblasts, prevents the osteolysis from ROS and inflammatory factors. As an alternative drug of osteoporosis, melatonin could improve gut ecology, remodel microbiota composition, regulate substance absorption and maintain metabolism balance, all of which was beneficial to the health of bone structure. In conclusion, our review systemically demonstrated the effects of melatonin in bone metabolism. Based on the evidences in this review, melatonin will play a more important role in the diagnosis, prevention and treatment for postmenopausal osteoporosis.